Land Suitability and Direction of Strategic Agricultural Commodities in East Kalimantan to Support the Development of the New Nation’s Capital of Republic of Indonesia - Sukarman Sukarman; Erna Suryani; Husnain Husnain (Jurnal Sumberdaya Lahan, 2021)
Abstract. The development of the new nation's capital in East Kalimantan must be supported with sufficient food supply. An Agricultural buffer zone must be provided as production area of food crops, horticulture, plantation, and livestock to suffice the food needs. The planning of landuse arrangement in the area required land suitability assessment for various agricultural commodities. The purpose of this paper is to provide information of land suitability in East Kalimantan Province that support the development plan of the new capital of the Republic of Indonesia. Literature studies of the previous research in East Kalimantan Province are carried out by the Indonesian Center for Agricultural Land Resources Research and Development (ICALRRD), as well as other research institutions. Based on the researches by ICALRRD conducted between year 2016-2019, the land suitable for agriculture is quite extensive (7.7 million ha), mostly for dry land farming. It is classified as suitable (S) mainly for plantation, forage, dry land food, horticulture, and upland rice, especially rainfed paddy. Only a small part is suitable for swamp lowland paddy field or tidal paddy field. The efforts to develop the regions include: (1) the expansion of new areas called as extensification (E), and a little through intensification (I). Extensification is conducted by cultivating superior commodities on new opening land that were previously in the form of shrubs or swampy shrubs, and open area or pasture. The available area for extensification program in East Kalimantan is 2.728 million ha. (2) The intensification program is carried out through the development of commodities in the existing land by strengthening the application of land technology, water management, crops varieties selection and cultivation techniques covering 73.2 thousand ha.Abstrak. Rencana pemindahan ibu kota negara ke Kalimantan Timur, perlu didukung oleh kawasan penyangga pertanian (tanaman pangan, hortikultura, perkebunan, dan peternakan) untuk memenuhi kebutuhan pangan masyarakat. Perencanaan penyusunan kawasan tersebut memerlukan data kesesuaian lahan berbagai komoditas pertanian. Tujuan dari tulisan ini adalah untuk memberikan informasi data tentang kesesuaian lahan di Provinsi Kalimantan Timur dalam mendukung rencana pembangunan ibukota baru Republik Indonesia. Metode yang digunakan dalam penulisan makalah ini adalah studi literatur dari hasil penelitian di Provinsi Kalimantan Timur, baik yang dilaksanakan oleh Balai Besar Litbang Sumberdaya Lahan Pertanian (BBSDLP), maupun lembaga penelitian lain. Berdasarkan data hasil penelitian BBSDLP antara tahun 2016-2019, lahan yang sesuai untuk pertanian cukup luas (7,7 juta ha), terutama untuk pertanian lahan kering. Lahan yang tergolong kelas sesuai (S) sebagian besar untuk tanaman perkebunan, pakan ternak, pertanian tanaman pangan lahan kering, hortikultura, dan padi sawah tadah hujan. Hanya sedikit yang sesuai untuk pertanian padi rawa lebak atau padi pasang surut. Upaya yang dapat ditempuh untuk membangun kawasan ini adalah: (1) melalui perluasan areal baru atau ekstensifikasi (E) tanaman perkebunan, pakan ternak, pertanian tanaman pangan lahan kering, hortikultura, dan padi sawah tadah hujan, pada lahan bukaan baru yang sebelumnya berupa semak belukar atau semak belukar rawa, lahan terbuka atau padang rumput seluas 2,728 juta ha. (2) melalui program intensifikasi (I) dilakukan melalui pengembangan komoditas di lahan sawah eksisting melalui penguatan aplikasi teknologi pengelolaan lahan, pengelolaan air, penggunaan varietas unggul, dan teknik budidaya, seluas 73,2 ribu ha.